Water rehydration capacity analysis of different types of dried fish products at different water temperature stored at ambient and refrigeration condition - Rana, Md Masud; Nushy, Nusrat Hossain; Sharmin, Sonia; Chakraborty, Subhash Chandra (Asian Journal of Medical and Biological Research, 2018)
Water rehydration capacity of the fishes named tengra (Mystus tengara) and batashi (Neotropious atherinoides) were studied in order to evaluate their eating quality. The initial value of protein, fat and ash content of Salt-Smoke-Dried (SSD) tengra and batashi was 63.40, 19.95 and 16.55%; 65.93, 17.09 and 16.90%, respectively on dry matter basis. Maximum Rehydration capacity obtained from salt-smoke-dried batashi and minimum value obtained from traditional dried tengra before storage at 280C temperature and its range varied between 17.68 to 50.38%. The reconstitution capacity of the products at 280C after the two month storage was in the range of 36.15 to 47.22% with minimum value for SSD tengra stored at ambient temperature after soaking 15 and maximum value obtained from SSD tengra stored at refrigeration temperature after 60 min soaking in water. After two month storage at 400C the water reconstitution capacity was in the range of 38.24 to 54.78% with lowest value for control dried (CD; treated without salt and smoke) tengra stored at ambient temperature after soaking 15 min and highest value obtained from SSD batashi stored at refrigeration temperature after soaking 60 min in water. On the other hand at 600C the reconstitution capacity after two month storage was in the range of 40.0 to 68.55% with minimum value for CD tengra stored at ambient temperature soaked after 15 min and maximum value for SSD batashi stored at refrigeration temperature soaked after 60 min in water. The reconstitution percentage was completely high at 600C after soaking for 60 min for most of the samples. Asian J. Med. Biol. Res. March 2018, 4(1): 21-26